Analysis Selection of The Work Methods Pier Head Cast in Situ Toll Road Bridge on Hilly Topography - Abdul Kholiq; Tri Joko Wahyu Adi (Syntax Corporation, 2022)
The implementation of construction projects must be managed professionally with good and appropriate management. One of them is through the selection of work methods in the implementation process. In bridge construction, several main parts, such as pier head construction, need special attention. This study aims to analyze the selection of the best work method in implementing pier head cast in situ in the construction of toll road projects from several alternative pier head work methods, including full shoring system, bracket truss system, and corbel truss systems. The best alternative method is selected using the AHP (Analytic Hierarchy Process) Method. Decision-making variables, which include four criteria and ten sub-criteria, were obtained from in-depth literature reviews and discussions with experts through FGD (Focus Group Discussion). From the results of the analysis using AHP, the values for corbel truss (0.530), full shoring (0.318), and bracket truss (0.152) were obtained. Compared to other alternatives, the corbel truss system method has advantages in duration, characteristics, and performance criteria. Hence, the corbel truss system method is the best alternative to be used as a pier head cast in situ bridge work method.